Current scenario of rational usage of various drugs in indoor patients - Saeed, Shaheen; Saeed, Parvez; Sharma, Varun (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Irrational prescribing of drugs is of common occurrence in clinical practice. Rational drug prescribing is defined as “the use of the least number of drugs to obtain the best possible effects in the shortest period and at a reasonable cost”. The present study was designed to evaluate the practice of rational prescription in patients (cases) admitted in various wards ofG.S.V.M.MedicalCollege and associated hospitals atKanpur. Methods: This study was carried out on patients admitted in different wards. For the study of drug prescribing patterns, each prescribed drug was counted only once for a patient, irrespective of change in dose and route of administration. WHO guidelines were taken into consideration. Both distribution of type of drug as well as drug category were evaluated in different departments thereafter. The characteristics chosen on each prescription provided the incidence of poly pharmacy and frequencies of prescribing of individual drug were analyzed. The data obtained were subsequently categorized systematically and analyzed by taking WHO guidelines into consideration. Results: The most commonly prescribed drugs were vitamins and tonics (57.5%) followed by anti-microbial agents (12.7%), non-steroidal anti-inflammatory drugs (10.5%), anti-hypertensive (5.2%), anti cough remedies and acid peptic disease drugs. Generic drug prescription was very low as most of drugs prescribed were proprietary. A low number of Fixed Dose Combinations (FDCs) were prescribed, this finding was in accordance with the WHO recommended list of FDCs. Items on the WHO model list of essential drugs were prescribed frequently. The use of drugs has been found to be in accordance with the disease, the patient had. Conclusions: Present study highlighted that there was a high incidence of irrational prescribing practice that increased with the total number of drugs per prescription.